Distributed Topology and Path Management Schemes for Wireless Multihop Networks - Shrespha, Deepesh Man (The Graduate School, Ajou University, 2009)
Wireless multi-hop networks are gaining widespread popularity in recent years due to ease of deployment, low cost and better performance. In this dissertation, we study different types of wireless multi-hop networks such as wireless local area network mesh (WLAN mesh), mobile ad hoc network (MANET), mobile multi-hop relay (MMR) network and the problems associated with such networks. In particular, we focus on the wireless multi-hop topology management and path selection schemes of these networks as they are challenged with the issue of selecting appropriate links for maintaining connectivity, reducing interference and constructing a network path. In the first section, we present the topology management protocols for constructing efficient network topology and compare them with the existing protocols. We show that the formation of topology based on the simple topological information such as node identification and degree can give a superior performance compared to other existing protocols. Simulations and testbed experiments indicate that the appropriate selection of subset of links and its use during the communication gives a better network throughput and reduces significant end-to-end latency. We investigate the capacity and scalability of such networking topologies and propose realizable protocols pertaining to the well known standards for wireless multi-hop communication. In the next section we propose two path selection protocols based on topology information and existing network parameters for MANETs and MMR networks. Under the mobile and static topology, path selection protocols have different issues and challenges. In MANET, mobility is of important concern, while in MMR networks fair utilization of bandwidth is important for accepting more connections. In both cases, we investigate the performance of the network in terms of throughput and latency. We introduce enhanced channel unification protocol (ECUP) that can be applied to the multi-channel IEEE 802.11s based WLAN mesh. Then we suggest a novel distributed channel assignment protocol for multi-interface, multi-channel IEEE 802.11 WLAN mesh. Our proposed channel assignment scheme for low interference topology (CLICT) not only utilizes multiple channels for reducing interference but also maintain the desirable network connectivity to avoid disconnection. While topology formation is important in wireless multi-hop network, based on the given topology efficient path selection protocols enhance actual network performance. We introduce enhancement in the path selection/routing protocol based on ad hoc on-demand vector routing protocol (AODV) for utilizing asymmetric links in the network topology. Our novel approach in this scheme utilizes the unidirectional links that are normally avoided by the conventional routing schemes. Finally, we propose a bandwidth adaptive path (BAP) selection protocol for the IEEE 802.16j based mobile multi-hop network. The IEEE 802.16j is recently proposed infrastructure wireless network for wireless metropolitan area networks. Our BAP is based on the fact that the network faces asymmetric load resulting into excessive bandwidth consumption in some parts where subscribers are high and being under-utilized where the load is low. In this work, we suggest signaling technique to exchange network information, path selection algorithm and the metric. Simulation study shows that the BAP protocol outperforms other known protocols.
학위논문(박사)--아주대학교 정보통신전문대학원 :정보통신공학과,2009. 2